(untitled) (Perner’s Contacts, 2011)
The paper deals with an increase of car traffic intensity within the area of Olomouc city and its neighborhoods. The aim of the research was temporal analysis of traffic volumes and the resulting changes compared with the spatial differentiation of suburbanization in the hinterland of the city of Olomouc. Input datasets were data traffic volumes of traffic census in 2000 and 2005 and field research of authors in 2010.